Keefektifan Solution-Focused Brief Group Counseling untuk Meningkatkan Motivasi Berprestasi Siswa Sekolah Menengah Kejuruan - Bambang Dibyo Wiyono (JKI (Jurnal Konseling Indonesia), 2015)
The quality of SMK graduates is influenced by the graduates’ competence attainment that is manifested in academic achievement. Some studies show that academic achievement is influenced by achievement motivation. Increasing motivation is expected to occur through the application of solution-focused brief group counseling. Solution-focused brief group counseling is based on postmodern and social constructivist philosophy. It also has brief characteristics, focused on solution, goal oriented, focused on the present and future time. The design of this study was applying pretest & posttest control group design. The subject in this study were X grade students of SMK Mambaul Ulum Bata-Bata Pamekasan who have low achievement motivation. The data were analyzed through TwoIndependent-Sample Test-Mann-Withney U. The results of this study shows that the counting value of z > z table, that is -2.619. Asymp value. Sig. (2-tailed) is 0.009 < 0.05. hence, Ho was rejected. It means that solution-focused brief group counseling is effective to enhance achievement motivation of vocational school students.